Pengaruh Profitabilitas, Leverage, dan Struktur Modal terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang terdaftar di BEI Periode 2020-2023 - Della Ayu Nur Sholichah; Nur Ainiyah; M. Bahril Ilmiddaviq (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study analyzes how firm value is affected by profitability, leverage, and capital structure in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. The food and beverage industry is the object of research due to its strategic importance to the Indonesian economy and its vulnerability to the COVID-19 pandemic. The associative quantitative design in this study used purposive sampling to select 29 companies that met the predetermined standards. The annual financial statements provided secondary data, which was analyzed using multiple linear regression analysis with SPSS version 22. The findings show that firm value is significantly positively affected by profitability as measured through Return on Assets (ROA), suggesting that higher profitability increases investor confidence. In contrast, when analyzed separately, capital structure (measured by debt-to-asset ratio) and leverage (measured by debt-to-equity ratio) show no significant effect. However, the three factors together have a substantial simultaneous effect on firm value. These results emphasize that, in the post-pandemic environment, profitability dominates investor perceptions and assessments of firm value.